Dopamine transporter (DAT) genetic hypofunction in mice produces alterations consistent with ADHD but not schizophrenia or bipolar disorder. (15th July 2017) - Mereu, M.; Contarini, G.; Buonaguro, E.F.; Latte, G.; Managò, F.; Iasevoli, F.; de Bartolomeis, A.; Papaleo, F.
Abstract: ADHD, schizophrenia and bipolar disorder are psychiatric diseases with a strong genetic component which share dopaminergic alterations. Dopamine transporter (DAT) genetics might be potentially implicated in all these disorders. However, in contrast to DAT absence, the effects of DAT hypofunction especially in developmental trajectories have been scarcely addressed. Thus, we comprehensively studied DAT hypofunctional mice (DAT+/-) from adolescence to adulthood to disentangle DAT-dependent alterations in the development of psychiatric-relevant phenotypes. From pre-adolescence onward, DAT+/- displayed a hyperactive phenotype, while responses to external stimuli and sensorimotor gating abilities were unaltered. General cognitive impairments in adolescent DAT+/- were partially ameliorated during adulthood in males but not in females. Despite this, attentional and impulsivity deficits were evident in DAT+/- adult males. At the molecular level, DAT+/- mice showed a reduced expression of Homer1a in the prefrontal cortex, while other brain regions as well as Arc and Homer1b expression were mostly unaffected. Amphetamine treatments reverted DAT+/- hyperactivity and rescued cognitive deficits. Moreover, amphetamine shifted DAT-dependent Homer1a altered expression from prefrontal cortex to striatal regions. These behavioral and molecular phenotypes indicate that a genetic-driven DAT hypofunction alters neurodevelopmental trajectories consistent with ADHD, but not with schizophrenia and bipolar disorders. Highlights: DAT hypofunction induces behavioral alterations from adolescence to adulthood. DAT hypofunction leads to hyperlocomotion, attentional and impulsivity deficits. DAT hypofunction alters Homer 1a and Arc expression in cortex and striatum. DAT hypofunction recapitulate ADHD-like phenotypes in mice. DAT hypofunction did not recapitulate schizophrenia-like phenotypes in mice.